Performance Optimization of Modified Gussasphalt Binder Prepared Using Natural Asphalt - Li, Tao; Jin, Qing; Jiang, Peng; Sun, Huadong; Ding, Yongling; Yan, Zongyao; Shi, Nan (Frontiers in Materials, 2022)
The advantageous thermal stability and construction workability of gussasphalt, a type of asphalt concrete, has drawn increasing attention. To prepare a type of superior gussasphalt concrete using Qingchuan rock asphalt (QRA), a modified gussasphalt binder was prepared with modifiers made up by different dose of styrene-butadiene-styrene, terpene resin, furfural extraction oil and SAW. Then, the rheological properties, microstructure, and thermal stability of gussasphalt binder were studied. The results indicated that the modifier #1 had significant effects on the other indexes but for the ductility, it was less effective in improving the low-temperature performance of the asphalt binder. The low-temperature performance of the binder with modifier #2 was superior compared with that of binder with modifier #1. The binder with 12.5% QRA and 5% modifier #2 can be regarded as an optimal collocation, which had a superior compatibility, high-temperature performance, and comprehensive temperature susceptibility.